Distractor onset but not preparation time affects the frequency of task confusions in task switching - Steinhauser, Marco; Gade, Miriam (Frontiers in Psychology, 2015)
When participants rapidly switch between tasks that share the same stimuli and responses, task confusions (i.e., the accidental application of the wrong task) can occur. The present study investigated whether these task confusions result from failures of endogenous control (i.e., from ineffective task preparation) or from failures of exogenous control (i.e., from stimulus-induced task conflicts). The frequency of task confusions was estimated by considering the relative proportion of distractor errors, that is, errors that result when participants erroneously respond to the distractor associated with the alternative task. In Experiment 1, the efficiency of exogenous control was manipulated by varying the temporal order of target and distractor presentation. In Experiment 2, the efficiency of endogenous control was manipulated by varying the time available for preparing the task in advance. It turned out that only the efficiency of exogenous control but not the efficiency of endogenous control influenced the proportion of distractor errors. Accordingly, task confusions are more related to failures in exogenous control.